The Influence of Family Environment, Social Media Utilization, Confidence, Motivation on Entrepreneurial Interest in Generation Z in Mataram City - Verren Regina Agustin; St. Maryam; Akung Daeng (West Science Journal Economic and Entrepreneurship, 2024)
In the development of the economy and the equitable distribution of income in a country, entrepreneurs have a big role in it. With the number of entrepreneurs increasing and continuing to increase, it marks that the country is a country with a developed economy. Currently, Generation Z is the largest generation so Generation Z will have an important role if their human resources are productive and competitive. This study aims to analyze the influence of family environment, social media utilization, confidence, and motivation on entrepreneurial interest in generation z. The population in this study is Generation Z in Mataram City. According to the latest data in 2022, the sample used was 100 respondents, research methods with quantitative methods, data collection techniques with questionnaires, data were processed with the help of IBM SPSS.27 test tools and the tests carried out were validity, reliability, classical assumptions, multiple linear regression analysis tests, and determination coefficients (R2). To test the hypothesis in this study, the F test (simultaneous) and the t test (partial). The results of the study showed that (1) There was a partial influence of family environment variables, social media utilization, confidence, and motivation on Generation Z's entrepreneurial interest in Mataram City (2) There was a simultaneous influence of family environment, social media utilization, confidence, and motivation on entrepreneurial interest.